Lithium manganese iron phosphate material with hollow-concentration gradient structure, preparation method of lithium manganese iron phosphate material, positive plate and battery
By designing a hollow-concentration gradient structure in lithium manganese ferrophosphate material, and using ionic conductive agents and carbon materials to improve conductivity, the problem of low conductivity and mobility of lithium manganese ferrophosphate material is solved, and the battery's magnification and cycling performance are significantly improved.
Patent Information
- Application Number
- CN202411722075.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-25
AI Technical Summary
The existing lithium manganese ferrophosphate materials have low electronic conductivity and lithium ion mobility, which leads to limited migration in electrochemical reactions, which in turn limits its application potential.
Lithium manganese ferrophosphate material with a hollow-concentration gradient structure is used, and an ionic conductive agent is introduced into the spherical shell as the core and carbon material is added to the shell layer to improve electronic conductivity, while a gradient concentration structure is designed in the core layer to stabilize the material structure.
Through hollow structure and gradient concentration design, the diffusion path of lithium ions and electron migration efficiency are improved, the structural stability of the material is enhanced, and the rate performance and cycling performance of the battery are improved.
Smart Images

Figure CN119695145A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to a lithium manganese iron phosphate material with a hollow-concentration gradient structure and a preparation method thereof, a positive electrode sheet, and a battery. Background Art
[0002] Lithium iron manganese phosphate is a solid solution of lithium iron phosphate and lithium manganese phosphate. Due to the incorporation of manganese ions with a high voltage platform, the voltage platform of lithium iron manganese phosphate reaches 4.1V, which is significantly higher than the voltage platform of lithium iron phosphate of 3.4V, that is, the energy density of lithium iron manganese phosphate is about 20% higher than that of lithium iron phosphate under the same design conditions. At the same time, due to the similar ionic radius and some chemical properties of manganese and iron, lithium iron manganese phosphate has a stable olivine structure, in which the PO4 tetrahedron is very stable and can play a structural support role during the charging and discharging process, so that lithium iron manganese phosphate has excellent thermodynamic and kinetic stability, that is, the safety of lithium iron manganese phosphate is better than that of NCM ternary materials. Therefore, lithium iron manganese phosphate has a better application scenario. However, lithium iron phosphate is a semiconductor, but after the addition of manganese elements, the value of its band gap width is significantly reduced, that is, lithium iron manganese phosphate is basically an insulator, with low electronic conductivity and low lithium ion mobility, which hinders the migration of electrons in electrochemical reactions and the migration of lithium ions, which in turn leads to limited application of lithium iron manganese phosphate.
[0003] At present, the electrochemical performance of lithium iron manganese phosphate is comprehensively improved mainly by regulating the ratio of manganese to iron, or by modifying the electrochemical performance of lithium iron manganese phosphate by nano-sizing, doping, coating and other modification technologies. For example, in the prior art (CN114725340A), a lithium iron manganese phosphate positive electrode material and a preparation method thereof are disclosed, wherein the lithium iron manganese phosphate positive electrode material comprises a lithium iron manganese phosphate core and a thin lithium iron phosphate coating layer coated on the surface of the core; and in the direction from the center of the lithium iron manganese phosphate core to the surface of the core, the content of manganese element decreases in a gradient and the content of iron element increases in a gradient. For another example, in the prior art (CN116364924A), a lithium iron manganese phosphate composite material and a positive electrode sheet and a battery comprising the same are disclosed, wherein the lithium iron manganese phosphate composite material comprises a core and a coating layer coating the core, the core comprises a lithium iron manganese phosphate material, and the coating layer comprises a carbon material and a solid electrolyte. However, the above modification method is difficult to effectively improve the cycle performance and rate performance of the lithium iron manganese phosphate material at the same time. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a lithium manganese iron phosphate material with a hollow-concentration gradient structure and a preparation method thereof, a positive electrode sheet, and a battery.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In the first aspect, the present invention provides a lithium manganese iron phosphate material having a hollow-concentration gradient structure (its structural schematic diagram is shown in Figure 1 As shown), the lithium iron manganese phosphate material is a hollow microsphere with open pores and / or closed pores, and the spherical shell of the hollow microsphere is mainly composed of lithium iron manganese phosphate particles;
[0007] The lithium iron manganese phosphate particles include an inner core (core), an inner core layer disposed on the surface of the inner core, and an outer shell layer disposed on the surface of the inner core layer;
[0008] The core is an ion conductive agent; the chemical formula of the core layer is LiMn x Fe 1-x-y M y PO4, wherein M is a doped metal element, 0<x<1, y≤0.2, 0<1-xy<1; along the direction from the inner core to the outer shell, the (molar) content of manganese element in the inner core layer decreases gradually, and the (molar) content of iron element increases gradually; the outer shell layer comprises a carbon material and an ion conductive agent;
[0009] The ion conductive agent includes at least one of a NASICON structure solid electrolyte and a perovskite solid electrolyte.
[0010] The lithium iron manganese phosphate material of the present invention is a hollow microsphere with open pores and / or closed pores. The hollow structure allows the electrolyte to enter the interior of the lithium iron manganese phosphate material particles, shortening the lithium ion diffusion path, thereby improving the rate performance of the battery; moreover, the spherical shell of the hollow microsphere is mainly composed of lithium iron manganese phosphate particles including an inner core, an inner core layer and an outer shell layer; using an ion conductive agent as the inner core can improve ion conductivity and promote ion diffusion; the inner core layer with a gradient concentration structure can not only inhibit the dissolution of manganese ions during the cycle, but also alleviate the volume change during the cycle, thereby enhancing the structural stability of the lithium iron manganese phosphate material; at the same time, using an ion conductive agent and an electronic conductive agent (carbon material) together as an outer shell layer can effectively promote the migration of ions / electrons, and serve as a protective layer to reduce the reaction with the electrolyte, further improving the structural stability of the lithium iron manganese phosphate material, thereby improving the electrochemical properties of the lithium iron manganese phosphate material, and then improving the rate performance and cycle performance of the battery.
[0011] As a preferred embodiment of the lithium manganese iron phosphate material having a hollow-concentration gradient structure of the present invention, at least one of the following conditions is satisfied:
[0012] a. The average particle size of the lithium iron manganese phosphate particles is 0.5-3 μm; optionally, the average particle size of the lithium iron manganese phosphate particles can be any one of 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or any two of the range values.
[0013] The study found that the lithium manganese iron phosphate particles in the above average particle size range not only have a suitable specific surface area to ensure that the electrolyte is in full contact with the positive and negative electrodes, thereby improving the reaction efficiency inside the battery and increasing the battery capacity; they can also better reduce the migration resistance of lithium ions in the electrolyte, thereby reducing the internal resistance of the battery, improving the battery's charge and discharge performance, and improving the battery's energy density and cycle life.
[0014] b. The average particle size of the core is 20 to 100 nm; optionally, the average particle size of the core can be any one of or any two of 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, and 100 nm.
[0015] The study found that the core with the above average particle size can not only better improve the ion conductivity and promote ion diffusion, but also enable the lithium manganese iron phosphate particles to maintain a higher proportion of active substances, thereby maintaining a higher battery energy density and enhancing the battery's endurance performance.
[0016] c. The average thickness of the outer shell layer is 20 to 100 nm; optionally, the average thickness of the outer shell layer can be any one or any two of 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, and 100 nm.
[0017] The study found that the outer shell layer with the above average thickness can better promote the migration of ions / electrons while effectively reducing the reaction with the electrolyte, thereby significantly improving the structural stability of the lithium manganese iron phosphate material.
[0018] As a preferred embodiment of the lithium manganese iron phosphate material with a hollow-concentration gradient structure of the present invention, the average particle size of the hollow microspheres is 2 to 15 μm; and / or the average thickness of the spherical shell of the hollow microspheres is 0.5 to 5 μm.
[0019] Optionally, the average particle size of the hollow microspheres can be any one of 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or any two of the range values; the average thickness of the spherical shell of the hollow microspheres can be any one of 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or any two of the range values.
[0020] The study found that the spherical shell of the above thickness can not only better prevent the internal voids of the hollow microspheres from being too large, which would cause the lithium manganese iron phosphate material to be easily crushed and affect the compaction density; it can also allow the electrolyte to fully enter the interior of the hollow microspheres, thereby effectively shortening the lithium ion diffusion path.
[0021] As a preferred embodiment of the lithium manganese iron phosphate material with a hollow-concentration gradient structure of the present invention, the mass fraction of the ion conductor in the lithium manganese iron phosphate material with a hollow-concentration gradient structure is 1.2% to 4.8%, and the mass fraction of the carbon material is 1.5% to 2.2%.
[0022] Optionally, the mass fraction of the ion conductor in the lithium manganese iron phosphate material with a hollow-concentration gradient structure is specifically 1.2%, 1.4%, 1.5%, 1.8%, 2.0%, 2.4%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 4.8%, or any two of the range values; the mass fraction of the carbon material can be specifically 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, or any two of the range values.
[0023] As a preferred embodiment of the lithium manganese iron phosphate material having a hollow-concentration gradient structure of the present invention, at least one of the following conditions is satisfied:
[0024] a. The NASICON structure solid electrolyte is at least one of lithium aluminum titanium phosphate (LATP) and lithium aluminum germanium phosphate (LAGP);
[0025] b. The perovskite-type solid electrolyte is lanthanum lithium titanate (LLTO);
[0026] c. The doped metal element is at least one of Ti, Mg, Al, Ni, Nb, Co, Cu, and Si.
[0027] In a second aspect, the present invention provides a method for preparing the above-mentioned lithium manganese iron phosphate material having a hollow-concentration gradient structure, comprising the following steps:
[0028] S1, adding a suspension of an ion conductive agent and a phosphorus source compound solution into a reaction container, and then continuously adding a mixed salt solution consisting of a manganese salt, an iron salt and a doping element salt into the reaction container to perform a precipitation reaction to form a phosphate precursor with ion conductive agent particles as nucleation points, aging, filtering, washing and drying to obtain precursor particles;
[0029] S2, mixing the precursor particles in S1 with a lithium source, a carbon source, an ion conductive agent and an additive, and granulating to obtain an intermediate product;
[0030] S3, in an atmosphere of an inert gas or a mixed gas of an inert gas and hydrogen, sintering the intermediate product in S2 at a high temperature to obtain a lithium manganese iron phosphate material having a hollow-concentration gradient structure;
[0031] The ion conductive agents in S1 and S2 are independently selected from at least one of NASICON structure solid electrolytes and perovskite type solid electrolytes.
[0032] It should also be noted that, as the precipitation reaction proceeds, the molar concentration of manganese salt in the mixed salt solution introduced into the reaction container in step S1 gradually decreases, and the molar concentration of iron salt gradually increases, so that the molar ratio of manganese to iron changes from 1:0 to 0:1, thereby causing the molar content of manganese element in the phosphate precursor wrapped on the surface of the ion conductive agent particles (nucleation points) to decrease gradually, and the molar content of iron element to increase gradually; the molar concentration of manganese salt and the molar concentration of iron salt in the mixed salt solution introduced into the reaction container can be regulated by mixing a mixed salt solution A1 with a high manganese salt content with a mixed salt solution A2 with a high iron salt content.
[0033] Optionally, the additive in step S2 includes at least one of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, and lithium phosphate.
[0034] As a preferred embodiment of the method for preparing the lithium iron manganese phosphate material of the present invention, at least one of the following conditions is met:
[0035] a. The temperature of the precipitation reaction in S1 is 20-80°C and the rotation speed is 100-800 rpm; optionally, the temperature of the precipitation reaction can be any one of 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or any two of the range values.
[0036] b. The aging temperature in S1 is 20-80°C and the time is 2-12h; optionally, the aging temperature can be any one of 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or any two of the range values, and the time can be any one of 2h, 4h, 6h, 8h, 10h, 12h or any two of the range values.
[0037] c. The high-temperature sintering temperature in S3 is 500-900°C, and the time is 6-20h; optionally, the high-temperature sintering temperature can be any one of 500°C, 600°C, 700°C, 800°C, 900°C or any two of the range values, and the time is any one of 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h or any two of the range values.
[0038] As a preferred embodiment of the method for preparing the lithium iron manganese phosphate material of the present invention, at least one of the following conditions is met:
[0039] a. The mass fraction of the ionic conductive agent in the suspension of the ionic conductive agent in S1 is 1% to 30%; optionally, the mass fraction of the ionic conductive agent can be any one of 1%, 5%, 10%, 15%, 20%, 25%, 30% or any two of the range values.
[0040] b. The concentration of the phosphorus source compound solution in S1 is 0.01 to 10 mol / L; optionally, the concentration of the phosphorus source compound solution can be any one of 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 3 mol / L, 5 mol / L, 7 mol / L, and 10 mol / L, or any two of the range values.
[0041] c. The phosphorus source compound in the phosphorus source compound solution in S1 includes at least one of phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
[0042] As a preferred embodiment of the method for preparing the lithium iron manganese phosphate material of the present invention, at least one of the following conditions is met:
[0043] a. The manganese salt in S1 includes at least one of manganese sulfate, manganese oxalate, manganese phosphate and manganese nitrate;
[0044] b. The iron salt in S1 includes at least one of ferrous sulfate, ferrous oxalate, ferrous nitrate and ferrous chloride;
[0045] c. The NASICON structure solid electrolyte in S1 is at least one of lithium aluminum titanium phosphate and lithium aluminum germanium phosphate; the chemical formula of the lithium aluminum titanium phosphate is Li 1+a Al a Ti 2-a (PO4)3, wherein 0≤a≤0.5; the chemical formula of the lithium germanium aluminum phosphate is Li 1+b Al b Ge 2-b (PO4)3, where 0≤b≤0.5;
[0046] Optionally, the lithium aluminum titanium phosphate (LATP) can be prepared by the following preparation method:
[0047] ① First, weigh lithium carbonate, aluminum oxide, titanium oxide, and ammonium dihydrogen phosphate according to the molecular stoichiometric ratio and mix them充分ly for 1 - 4 h; ② Subject the mixed raw materials to high-temperature heat treatment at 800 - 950 °C for a heat treatment time and keep them at a constant temperature for 6 - 20 h; ③ Crush the LATP block into micron-sized powder by ball milling, disperse it in an aqueous solution, with a ball milling speed of 200 - 500 rpm and a ball milling time of 4 - 20 h, adjusted according to the target particle size required; ④ Dry the slurry and then grind and crush it to obtain the target powder.
[0048] Optionally, the above-mentioned lithium germanium phosphate (LAGP) can be prepared by the following method:
[0049] ① First, weigh lithium carbonate, germanium oxide, aluminum oxide, and ammonium dihydrogen phosphate according to the molecular stoichiometric ratio and mix them充分ly for 2 - 8 h; ② Subject the mixed raw materials to high-temperature heat treatment at 700 - 900 °C for a heat treatment time and keep them at a constant temperature for 6 - 20 h; ③ Crush the LAGP block into micron-sized powder by ball milling, disperse it in an aqueous dispersion, with a ball milling speed of 100 - 700 rpm and a ball milling time of 3 - 24 h, adjusted according to the target particle size required; ④ Dry the slurry and then grind and crush it to obtain the target powder.
[0050] d. The perovskite-type solid electrolyte described in S1 is lithium lanthanum titanate, and the chemical formula of the lithium lanthanum titanate is Li 3c La 2 / 3-c Ti d T 1-d O3, where 0 < c < 2 / 3, 0 < d ≤ 1, and T is at least one of Nb, W, Ti, Hf, Ru, Mo, Nd, Ba, Ga, In, Ge, Sn, Sb, Se;
[0051] Optionally, the above-mentioned lithium lanthanum titanate (LLTO) can be prepared by the following method:
[0052] ① First, weigh lithium carbonate, lanthanum oxide, and titanium oxide according to the molecular stoichiometric ratio and mix them充分ly for 2 - 12 h; ② Subject the mixed raw materials to high-temperature heat treatment at 1000 - 1200 °C for a heat treatment time and keep them at a constant temperature for 6 - 20 h; ③ Crush the LLTO block into micron-sized powder by ball milling, disperse it in an aqueous dispersion, with a ball milling speed of 100 - 600 rpm and a ball milling time of 2 - 24 h, adjusted according to the target particle size required; ④ Dry the slurry and then grind and crush it to obtain the target powder.
[0053] e. The doping element in the doping element salt described in S1 is at least one of Ti, Mg, Al, Ni, Nb, Co, Cu, Si.
[0054] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a coating disposed on at least one side of the current collector, wherein the coating comprises the above-mentioned lithium manganese iron phosphate material having a hollow-concentration gradient structure.
[0055] In a fourth aspect, the present invention provides a battery, comprising the above-mentioned positive electrode sheet.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The lithium iron manganese phosphate material of the present invention is a hollow microsphere with open pores and / or closed pores. The hollow structure allows the electrolyte to enter the interior of the lithium iron manganese phosphate material particles, shortening the lithium ion diffusion path, thereby improving the rate performance of the battery; moreover, the spherical shell of the hollow microsphere is mainly composed of lithium iron manganese phosphate particles including an inner core, an inner core layer and an outer shell layer; using an ion conductive agent as the inner core can improve ion conductivity and promote ion diffusion; the inner core layer with a gradient concentration structure can not only inhibit the dissolution of manganese ions during the cycle, but also alleviate the volume change during the cycle, thereby enhancing the structural stability of the lithium iron manganese phosphate material; at the same time, using an ion conductive agent and an electronic conductive agent (carbon material) together as an outer shell layer can effectively promote the migration of ions / electrons, and serve as a protective layer to reduce the reaction with the electrolyte, further improving the structural stability of the lithium iron manganese phosphate material, thereby improving the electrochemical properties of the lithium iron manganese phosphate material, and then improving the rate performance and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 It is a schematic structural diagram of the lithium iron manganese phosphate material of the present invention;
[0059] Figure 2 This is a SEM image of the lithium iron manganese phosphate material in Example 1;
[0060] Figure 3 is a particle size distribution curve of the phosphate precursor in Example 1;
[0061] Figure 4 This is a charge and discharge curve diagram of the lithium manganese iron phosphate material in Example 1;
[0062] Figure 5 This is a 500-cycle diagram of the lithium manganese iron phosphate material in Example 1. DETAILED DESCRIPTION
[0063] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0064] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.
[0065] 1. Li1.2 Al 0.2 Ti 1.8 (PO4)3, prepared by the following preparation method:
[0066] Lithium carbonate, aluminum oxide, titanium oxide, and ammonium dihydrogen phosphate were weighed according to the molecular weight ratio (i.e., the molar ratio of lithium carbonate, aluminum oxide, titanium oxide, and ammonium dihydrogen phosphate was 0.6:0.1:1.8:3), mixed evenly, and heat treated at 900°C for 10 hours to obtain Li 1.2 Al 0.2 Ti 1.8 (PO4)3; add 600g of Li in 1000mL of water 1.2 Al 0.2 Ti 1.8 (PO4)3 was ball milled at 500 rpm for 16 h, dried, and ground to obtain Li with an average particle size of 50 nm. 1.2 Al 0.2 Ti 1.8 (PO4)3.
[0067] 2. Li 1.2 Al 0.2 Ge 1.8 (PO4)3, prepared by the following preparation method:
[0068] Lithium carbonate, germanium oxide, aluminum oxide, and ammonium dihydrogen phosphate were weighed according to the molecular weight ratio (i.e., the molar ratio of lithium carbonate, germanium oxide, aluminum oxide, and ammonium dihydrogen phosphate was 0.6:0.1:1.8:3), mixed evenly, and heat treated at 800°C for 15h to obtain Li 1.2 Al 0.2 Ge 1.8 (PO4)3; add 600g of Li in 1000mL of water 1.2 Al 0.2 Ge 1.8 (PO4)3 was ball milled at 500 rpm for 16 h, dried, and ground to obtain Li with an average particle size of 50 nm. 1.2 Al 0.2 Ge 1.8 (PO4)3.
[0069] 3. Li 0.5 La 0.5 TiO3 is prepared by the following preparation method:
[0070] Lithium carbonate, lanthanum oxide, and titanium oxide were weighed according to the molecular weight ratio (i.e., the molar ratio of lithium carbonate, lanthanum oxide, and titanium oxide was 0.25:0.25:1), mixed evenly, and heat treated at 1200°C for 8h to obtain Li 0.5 La 0.5TiO3; add 600g of Li in 1000mL of water 0.5 La 0.5 TiO3 was ball-milled at 500 rpm for 16 h, dried, and ground to obtain Li with an average particle size of 50 nm. 0.5 La 0.5 TiO3.
[0071] Example 1
[0072] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and a preparation method thereof comprises the following steps:
[0073] S1, 12.06 mol of manganese sulfate, 0.036 mol of magnesium sulfate, 0.024 mol of titanium sulfate and water are prepared into a mixed salt solution A1 with a concentration of 2 mol / L, wherein the molar ratio of each metal element in the mixed salt solution A1 is Mn:Mg:Ti=0.995:0.003:0.002; 7.94 mol of ferrous sulfate, 0.024 mol of magnesium sulfate, 0.016 mol of titanium sulfate and water are prepared into a mixed salt solution A2 with a concentration of 2 mol / L, wherein the molar ratio of each metal element in the mixed salt solution A2 is Fe:Mg:Ti=0.995:0.003:0.002;
[0074] The mass fraction of 5% Li 0.5 La 0.5 TiO3(Li 0.5 La 0.5 The total mass of TiO3 is 13.70g, which is equivalent to a mass fraction of the core in the entire phosphate precursor of 0.4%) suspension (the solvent is water), 21mol of ammonium dihydrogen phosphate and water as a base liquid are added to a reaction container, and an appropriate amount of ammonia water with a concentration of 2mol / L is added to adjust the pH of the solution to 6.0±0.1; at the same time, ultrasonic waves are started to disperse the particles, and nitrogen is introduced to exclude the air in the reaction container; then the mixed salt solution A1 and the ammonia water are added to the reaction container in parallel, and at the same time, the mixed salt solution A2 is continuously added to the mixed solution A1, so that the molar ratio of manganese element to iron element in the mixture (the mixture of mixed solution A1 and mixed solution A2) entering the reactor gradually changes from 1:0 to 0:1;
[0075] The pH of the reaction solution was adjusted to 6.0±0.1 by changing the rate of adding ammonia water, the reaction temperature was 50°C, and the stirring speed was 450 rpm. 0.5 La 0.5When the particle size of the phosphate precursor with TiO3 as the nucleation point is 1.0-1.5 μm, stop adding the material and age it for 4 hours to completely precipitate the metal ions in the solution; wash and filter the phosphate precursor slurry several times, dry it in a vacuum drying oven at 100°C overnight, and obtain a phosphate precursor (wherein the molar ratio of manganese, iron, magnesium and titanium is 0.6:0.395:0.003:0.002).
[0076] S2, 1500g of phosphate precursor particles in S1, 319.36g of lithium carbonate (Li2CO3), 94.56g of glucose, 9.36g of carbon nanotubes (CNT), 28.60g of Li 0.5 La 0.5 TiO3 and 4.25 g of lithium dihydrogen phosphate were uniformly mixed and granulated to obtain an intermediate product.
[0077] S3, put the intermediate product in S2 into a quartz sagger and place it in a box furnace, heat it to 640°C at a rate of 5°C / min under nitrogen protection, sinter it for 10 hours, and cool it to room temperature to obtain a lithium manganese iron phosphate material with a hollow-concentration gradient structure (the mass fraction of carbon material in the lithium manganese iron phosphate material is 1.8%, Li 0.5 La 0.5 The mass fraction of TiO3 is 2%).
[0078] The ratio of the total amount of manganese (Mn) and iron (Fe) in the phosphate precursor, the amount of lithium (Li) in the lithium source, and the total amount of phosphorus (P) in the phosphate precursor and the phosphorus source is 1:1.05:1.02.
[0079] Example 2
[0080] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0081] Li in step S1 0.5 La 0.5 The mass fraction of TiO3 suspension is 5%, Li 0.5 La 0.5 The total mass of TiO3 is 3.42 g (ie, the mass fraction of the core in the entire phosphate precursor is 0.2%).
[0082] Example 3
[0083] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0084] Li in step S1 0.5 La0.5 The mass fraction of TiO3 suspension is 10%, Li 0.5 La 0.5 The total mass of TiO3 is 27.51 g (ie, the mass fraction of the core in the entire phosphate precursor is 0.8%).
[0085] Example 4
[0086] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0087] Li in step S1 0.5 La 0.5 TiO3 replaced by Li 1.2 Al 0.2 Ge 1.8 (PO4)3.
[0088] Example 5
[0089] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0090] Li in step S1 0.5 La 0.5 TiO3 replaced by Li 1.2 Al 0.2 Ti 1.8 (PO4)3.
[0091] Example 6
[0092] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0093] The mixed salt solution A1 in step S1 is composed of 6.68 mol of manganese sulfate, 0.020 mol of magnesium sulfate, 0.013 mol of titanium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Mg:Ti=0.995:0.003:0.002;
[0094] The mixed salt solution A2 in step S1 is composed of 5.31 mol of manganese sulfate, 7.90 mol of ferrous sulfate, 0.040 mol of magnesium sulfate, 0.026 mol of titanium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Fe:Mg:Ti=0.4:0.595:0.003:0.002;
[0095] The molar ratio of manganese, iron, magnesium and titanium in the prepared phosphate precursor is 0.6:0.395:0.003:0.002.
[0096] Example 7
[0097] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0098] The mixed salt solution A1 in step S1 is composed of 9.33 mol of manganese sulfate, 3.93 mol of ferrous sulfate, 0.040 mol of magnesium sulfate, 0.027 mol of titanium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Fe:Mg:Ti=0.7:0.295:0.003:0.002;
[0099] The mixed salt solution A2 in step S1 is composed of 2.67 mol of manganese sulfate, 3.97 mol of ferrous sulfate, 0.020 mol of magnesium sulfate, 0.013 mol of titanium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Fe:Mg:Ti=0.4:0.595:0.003:0.002;
[0100] The molar ratio of manganese, iron, magnesium and titanium in the prepared phosphate precursor is 0.6:0.395:0.003:0.002.
[0101] Example 8
[0102] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that: the particle size of the phosphate precursor is 2.0-4.0 μm.
[0103] In step S1, no ultrasonic dispersion treatment is performed, that is, the specific operation is: Li 0.5 La 0.5 TiO3(Li 0.5 La 0.5 A suspension (the solvent is water) of TiO3 with a total mass of 13.70 g), 21 mol of ammonium dihydrogen phosphate and water as the base liquid are added to the reaction container, and an appropriate amount of 2 mol / L ammonia water is added to adjust the pH of the solution to 6.0±0.1; at the same time, nitrogen is introduced to exclude the air in the reaction container.
[0104] Example 9
[0105] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that: the particle size of the phosphate precursor is 4.0-6.0 μm.
[0106] The base solution in step S1 does not contain ammonium dihydrogen phosphate, that is, the specific operation is: add 5% by mass of Li 0.5 La 0.5 TiO3(Li 0.5 La 0.5 The total mass of TiO3 is 13.70g) suspension (solvent is water) and water as the base liquid are added to the reaction container, and an appropriate amount of ammonia water with a concentration of 2 mol / L is added to adjust the pH of the solution to 6.0±0.1; at the same time, ultrasonic wave is started to disperse the particles, and nitrogen is introduced to remove the air in the reaction container.
[0107] Example 10
[0108] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that: the particle size of the phosphate precursor is 9.0-10.0 μm.
[0109] The base liquid in step S1 does not contain ammonium dihydrogen phosphate and is not subjected to ultrasonic dispersion treatment. The specific operation is: Li 0.5 La 0.5 TiO3(Li 0.5 La 0.5 A suspension (solvent is water) of TiO3 with a total mass of 13.70 g) and water as a base liquid are added to a reaction container, and an appropriate amount of 2 mol / L ammonia water is added to adjust the pH of the solution to 6.0±0.1; nitrogen is introduced at the same time to remove the air in the reaction container.
[0110] Embodiment 11
[0111] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0112] The mixed salt solution A1 in step S1 is composed of 12.06 mol of manganese sulfate, 0.060 mol of copper sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Cu=0.995:0.005;
[0113] The mixed salt solution A2 in step S1 is composed of 7.94 mol of manganese sulfate, 0.040 mol of copper sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Fe:Cu=0.995:0.005;
[0114] The molar ratio of manganese, iron and copper in the prepared phosphate precursor is 0.6:0.395:0.005.
[0115] Example 12
[0116] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0117] The mixed salt solution A1 in step S1 is composed of 12.06 mol of manganese sulfate, 0.060 mol of nickel sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Ni=0.995:0.005;
[0118] The mixed salt solution A2 in step S1 is composed of 7.94 mol of manganese sulfate, 0.040 mol of nickel sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Fe:Ni=0.995:0.005;
[0119] The molar ratio of manganese, iron and nickel in the prepared phosphate precursor is 0.6:0.395:0.005.
[0120] Embodiment 13
[0121] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0122] The mixed salt solution A1 in step S1 is composed of 12.06 mol of manganese sulfate, 0.060 mol of magnesium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Mg=0.995:0.005;
[0123] The mixed salt solution A2 in step S1 is composed of 7.94 mol of manganese sulfate, 0.040 mol of magnesium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Fe:Mg=0.995:0.005;
[0124] The molar ratio of manganese, iron and magnesium in the prepared phosphate precursor is 0.6:0.395:0.005.
[0125] Embodiment 14
[0126] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0127] The mixed salt solution A1 in step S1 is composed of 12.06 mol of manganese sulfate, 0.060 mol of titanium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Ti=0.995:0.005;
[0128] The mixed salt solution A2 in step S1 is composed of 7.94 mol of manganese sulfate, 0.040 mol of titanium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Fe:Ti=0.995:0.005;
[0129] The molar ratio of manganese, iron and titanium in the prepared phosphate precursor is 0.6:0.395:0.005.
[0130] Embodiment 15
[0131] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0132] The carbon source in step S2 is 94.56 g of glucose and 9.36 g of graphene, and the mass fraction of the carbon material in the lithium manganese iron phosphate material prepared in step S3 is 1.8%.
[0133] Example 16
[0134] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0135] The carbon source in step S2 is 118.20 g of glucose, and the mass fraction of the carbon material in the lithium manganese iron phosphate material prepared in step S3 is 1.8%.
[0136] Embodiment 17
[0137] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0138] The carbon source in step S2 is 111.16 g of sucrose, and the mass fraction of the carbon material in the lithium manganese iron phosphate material prepared in step S3 is 1.8%.
[0139] Embodiment 18
[0140] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0141] In step S2, Li 0.5 La 0.5 The amount of TiO3 used is 21.34 g, and the lithium manganese iron phosphate material prepared in step S3 has a Li 0.5 La 0.5 The mass fraction of TiO3 is 1.5%.
[0142] Embodiment 19
[0143] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0144] In step S2, Li 0.5 La 0.5 The amount of TiO3 used is 43.35 g, and the lithium manganese iron phosphate material prepared in step S3 has a Li 0.5 La 0.5 The mass fraction of TiO3 is 3%.
[0145] Embodiment 20
[0146] This embodiment provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0147] Step S2 is: 1500g of the phosphate precursor particles in S1, 319.36g of lithium carbonate (Li2CO3), 94.56g of glucose, 9.36g of carbon nanotubes (CNT), 13.70g of Li 0.5 La 0.5 TiO3 and 4.25 g of lithium dihydrogen phosphate were uniformly mixed to obtain an intermediate product (ie, without granulation).
[0148] Embodiment 21
[0149] This comparative example provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0150] Li in step S1 0.5 La 0.5 The mass fraction of TiO3 suspension is 10%, Li 0.5 La 0.5 The total mass of TiO3 is 34.45 g (ie, equivalent to a mass fraction of the core in the entire phosphate precursor of 1%).
[0151] Comparative Example 1
[0152] This comparative example provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0153] Li in step S1 0.5 La 0.5 The mass fraction of TiO3 suspension is 0%, Li 0.5 La 0.5 The total mass of TiO3 is 0g.
[0154] Comparative Example 2
[0155] This comparative example provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0156] The mixed salt solution A1 in step S1 is composed of 6.00 mol of manganese sulfate, 3.95 mol of ferrous sulfate, 0.03 mol of magnesium sulfate, 0.02 mol of titanium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Fe:Mg:Ti=0.6:0.395:0.003:0.002;
[0157] The mixed salt solution A2 in step S1 is composed of 6.00 mol of manganese sulfate, 3.95 mol of ferrous sulfate, 0.03 mol of magnesium sulfate, 0.02 mol of titanium sulfate and water, with a concentration of 2 mol / L, wherein the molar ratio of each metal element is Mn:Fe:Mg:Ti=0.6:0.395:0.003:0.002;
[0158] The molar ratio of manganese, iron, magnesium and titanium in the prepared phosphate precursor is 0.6:0.395:0.003:0.002.
[0159] Comparative Example 3
[0160] This comparative example provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1, except that:
[0161] The mixed salt solution A1 in step S1 is composed of 12.0 mol of manganese sulfate and water, with a concentration of 2 mol / L;
[0162] The mixed salt solution A2 in step S1 is composed of 8.0 mol of ferric sulfate and water, with a concentration of 2 mol / L;
[0163] The molar ratio of manganese to iron in the prepared phosphate precursor is 0.6:0.4.
[0164] Comparative Example 4
[0165] This comparative example provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1:
[0166] In step S2, Li 0.5 La 0.5 The amount of TiO3 used is 73.77 g, and the amount of Li in the lithium manganese iron phosphate material prepared in step S3 is 0.5 La 0.5 The mass fraction of TiO3 is 5%.
[0167] Comparative Example 5
[0168] This comparative example provides a lithium manganese iron phosphate material with a hollow-concentration gradient structure, and its preparation method is basically the same as that of Example 1:
[0169] In step S2, Li 0.5 La 0.5 The amount of TiO3 used is 0g, and the lithium manganese iron phosphate material prepared in step S3 has Li 0.5 La 0.5 The mass fraction of TiO3 is 0.98%.
[0170] Performance Testing
[0171] 1) SEM test
[0172] according to Figure 2 It can be seen that the lithium manganese iron phosphate material in Example 1 is a spherical or quasi-spherical particle with a hollow structure inside, and the spherical or quasi-spherical particle is composed of particles with a smaller particle size, which indicates that the lithium manganese iron phosphate material of the present invention is a hollow microsphere with open or closed pores.
[0173] 2) Particle size test
[0174] The phosphate precursor prepared in step S1 of Example 1 was tested for particle size using a Malvern 3000 laser average particle size tester. The test results are as follows: Figure 3 As shown, through Figure 3 From the particle size distribution curve of the phosphate precursor, it can be seen that the average particle size (D50) of the phosphate precursor is about 1 μm, and the particle size distribution curve is normally distributed, indicating that the phosphate precursor particles are small under ultrasonic dispersion, and the particle size distribution is uniform and the particle consistency is good.
[0175] 3) Conductivity and compaction density test
[0176] The conductivity and compaction density of the lithium manganese iron phosphate material with a hollow-concentration gradient structure in each embodiment and comparative example were tested using a PRCD3100 powder resistivity & compaction density meter. The test results are shown in Table 2.
[0177] 4) Cycle performance test
[0178] The lithium manganese iron phosphate material with a hollow-concentration gradient structure in each embodiment and comparative example is used as a positive electrode active material to prepare a positive electrode sheet and assemble it into a lithium ion battery, which specifically includes the following steps:
[0179] Preparation of positive electrode sheet: The positive electrode active material, conductive carbon black (SP) and binder polyvinylidene fluoride (PVDF) are weighed in a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) is used as a solvent, and the mixture is ball-milled in a planetary ball mill for 2 hours to prepare a positive electrode slurry; then the slurry is coated on an aluminum foil current collector, dried, rolled and punched into a positive electrode sheet, placed in a vacuum drying oven for 12 hours, and then placed in a glove box under an inert gas protective atmosphere for use.
[0180] The negative electrode sheet is a metallic lithium sheet, the electrolyte is 1M LiPF6 (the solvent is a compound of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1), the separator is a polypropylene microporous membrane Celgard2300, and they are assembled into a CR2032 button cell.
[0181] Under the condition of 25℃±2℃, a battery testing system (Blue Electric series battery testing system) was used to carry out a charge-discharge cycle test on the above-mentioned CR2032 button battery; the test conditions are as follows: the charge and discharge rates are 0.1C, 1C, and 8C, respectively, the voltage range is 2.5V~4.3V, and one charge and discharge is regarded as one cycle; the charge specific capacity, discharge specific capacity, first charge and discharge efficiency (i.e., the first cycle coulomb efficiency) and capacity retention rate after 500 cycles = discharge specific capacity of the 500th cycle / discharge specific capacity of the first cycle × 100% were recorded.
[0182] Table 2 Performance of lithium iron manganese phosphate positive electrode materials and corresponding batteries in various embodiments and comparative examples
[0183]
[0184]
[0185] According to the data in Table 2, Figure 4 and Figure 5 It can be seen that the conductivity of the lithium manganese iron phosphate positive electrode material in Examples 1 to 21 reaches 7.49×10 -2 ~11.78×10 -2 S / cm, compacted density reaches 2.30~2.39g / cm 3 , 0.1C discharge specific capacity reaches 151.55-159.52 mAh / g, the first charge and discharge efficiency is ≥95.26%, the capacity retention rate after 1C cycle 500 times reaches 90.77%-99.96%, and the 8C discharge specific capacity reaches 119.26-135.21 mAh / g, indicating that the lithium manganese iron phosphate positive electrode material with a hollow-concentration gradient structure of the present invention has excellent cycle stability and rate performance.
[0186] Among them, the concentration gradient structure alleviates the problem of easy dissolution of manganese ions during the cycle, and at the same time alleviates the volume change during the cycle, enhances the structural stability of the material, and improves the cycle stability of the material; the hollow structure enables the electrolyte to penetrate into the interior of the particles, shortens the diffusion path of lithium ions, and improves the rate performance of the material; the addition of ion conductive agents can improve the conductivity of the material and improve the rate performance of the material, among which LLTO has a more obvious improvement in conductivity; doping elements can also improve the conductivity of lithium iron manganese phosphate and enhance the structural stability of the material, especially the co-doping of Mg and Ti elements has a more obvious effect on improving the conductivity of lithium iron manganese phosphate, improving the structural stability and rate performance; different carbon sources will also affect the conductivity and electrochemical properties of the material, among which glucose and CNT have a more obvious improvement in material performance.
[0187] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A lithium manganese iron phosphate material having a hollow-concentration gradient structure, characterized in that: The lithium iron manganese phosphate material is a hollow microsphere with open pores and / or closed pores, and the spherical shell of the hollow microsphere is mainly composed of lithium iron manganese phosphate particles; The lithium iron manganese phosphate particles include a core, a core layer disposed on the surface of the core, and a shell layer disposed on the surface of the core layer; The core is an ion conductive agent; the chemical formula of the core layer is LiMn x Fe 1-x-y M y PO4, wherein M is a doped metal element, 0<x<1, y≤0.2, 0<1-xy<1; along the direction from the inner core to the outer shell, the content of manganese in the inner core layer decreases gradually, and the content of iron increases gradually; the outer shell layer includes a carbon material and an ion conductive agent; The ion conductive agent includes at least one of a NASICON structure solid electrolyte and a perovskite solid electrolyte.
2. The lithium iron manganese phosphate material according to claim 1, characterized in that: Satisfy at least one of the following: a. The average particle size of the lithium manganese iron phosphate particles is 0.5 to 3 μm; b. The average particle size of the core is 20 to 100 nm; c. The average thickness of the outer shell layer is 20 to 100 nm.
3. The lithium iron manganese phosphate material according to claim 1, characterized in that: The particle size of the hollow microspheres is 2 to 15 μm; and / or the average thickness of the spherical shell of the hollow microspheres is 0.5 to 5.0 μm.
4. The lithium iron manganese phosphate material according to claim 1, characterized in that: Satisfy at least one of the following: a. The NASICON structure solid electrolyte is at least one of lithium aluminum titanium phosphate and lithium aluminum germanium phosphate; b. The perovskite-type solid electrolyte is lithium lanthanum titanate; c. The doped metal element is at least one of Ti, Mg, Al, Ni, Nb, Co, Cu, and Si.
5. The method for preparing the lithium manganese iron phosphate material having a hollow-concentration gradient structure according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, adding a suspension of an ion conductive agent and a phosphorus source compound solution into a reaction container, and then continuously adding a mixed salt solution consisting of a manganese salt, an iron salt and a doping element salt into the reaction container to perform a precipitation reaction to form a phosphate precursor with ion conductive agent particles as nucleation points, aging, filtering, washing and drying to obtain precursor particles; S2, mixing the precursor particles in S1 with a lithium source, a carbon source, an ion conductive agent and an additive, and granulating to obtain an intermediate product; S3, in an atmosphere of an inert gas or a mixed gas of an inert gas and hydrogen, sintering the intermediate product in S2 at a high temperature to obtain a lithium manganese iron phosphate material having a hollow-concentration gradient structure; The ion conductive agents in S1 and S2 are independently selected from at least one of NASICON structure solid electrolytes and perovskite type solid electrolytes.
6. The preparation method according to claim 5, characterized in that: Satisfy at least one of the following: a. The temperature of the precipitation reaction in S1 is 20-80°C and the rotation speed is 100-800 rpm; b. The aging temperature in S1 is 20 to 80° C. and the aging time is 2 to 12 hours; c. The high temperature sintering in S3 is performed at a temperature of 500 to 900° C. and for a time of 6 to 20 hours.
7. The preparation method according to claim 5, characterized in that: Satisfy at least one of the following: a. The mass fraction of the ionic conductive agent in the suspension of the ionic conductive agent in S1 is 1% to 30%; b. The concentration of the phosphorus source compound solution in S1 is 0.01 to 10 mol / L; c. The phosphorus source compound in the phosphorus source compound solution in S1 includes at least one of phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
8. The preparation method according to claim 5, characterized in that: Satisfy at least one of the following: a. The manganese salt in S1 includes at least one of manganese sulfate, manganese oxalate, manganese phosphate and manganese nitrate; b. The iron salt in S1 includes at least one of ferrous sulfate, ferrous oxalate, ferrous nitrate and ferrous chloride; c. The NASICON structure solid electrolyte in S1 is at least one of lithium aluminum titanium phosphate and lithium aluminum germanium phosphate; the chemical formula of the lithium aluminum titanium phosphate is Li 1+a Al a Ti 2-a (PO4)3, wherein 0≤a≤0.5; the chemical formula of the lithium germanium aluminum phosphate is Li 1+ b Al b Ge 2-b (PO4)3, where 0≤b≤0.5; d. The perovskite-type solid electrolyte described in S1 is lithium lanthanum titanate, and the chemical formula of the lithium lanthanum titanate is Li 3c La 2 / 3- c Ti d T 1-d O3, where 0 < c < 2 / 3, 0 < d ≤ 1, and T is at least one of Nb, W, Ti, Hf, Ru, Mo, Nd, Ba, Ga, In, Ge, Sn, Sb, Se; e. The doping element in the doping element salt in S1 is at least one of Ti, Mg, Al, Ni, Nb, Co, Cu, and Si.
9. A positive electrode sheet, characterized in that: The invention comprises a current collector and a coating disposed on at least one side of the current collector, wherein the coating comprises the lithium manganese iron phosphate material with a hollow-concentration gradient structure as claimed in any one of claims 1 to 4.
10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Lithium ferric manganese phosphate positive electrode material with iron and manganese elements in full-concentration gradient distribution and preparation method of lithium ferric manganese phosphate positive electrode material
CN114725340A
Lithium manganese iron phosphate composite material and positive plate and battery comprising same
CN116364924A
Cathode material LiMn1-xFexPO4 for lithium ion cell and preparation method of cathode material LiMn1-xFexPO4
CN104577119A
Lithium manganese ferric phosphate (LMFP) material with core-cell structure as well as preparation method and application thereof
CN106299296A
Lithium iron phosphate material and preparation method thereof
CN111740101A